Crystal structure of potassium trifluoro[1,3-dithiano]borate, K(C 4S2H7BF3) - Stefani, H. A.; Cella, R.; Zukerman-Schpector, J.; Caracelli, I. [UNESP] (De Gruyter, 2006)
C4H7BF3KS2, monoclinic, P121/c1 (no. 14), a = 14.7374(3) Å, b = 9.0612(1) Å, c = 13.5805(2) Å, β = 98.964(4)°, V = 1791.4 Å3, Z = 8, Rgt(F) = 0.029, wRref(F2) = 0.010, T = 296 K. © by Oldenbourg Wissenschaftsverlag.